In Memoriam – Dr. Sorin-Corneliu Rădan (1945-2018) (Geo-Eco-Marina, 2019)
On Sunday, November 11, 2018, our good and beloved colleague Sorin-Corneliu Rădan passed away. He was my younger brother. He IS my younger brother. He was, is, and will remain my best and closest collaborator. It is difficult to write an article in memoriam for somebody who was so close, not only through professional ties, but also through blood ties, and to remain unbiased. For me, it is hard to talk about him in the past. Our lives and careers have been intertwined. At a distance of nearly two years, we went through the same kindergarten, the same school and the same faculty. Here we have separated, I followed geology, he, a math enthusiast since high school, chose geophysics. We started working in two different research institutes, that are today unified under the Geological Institute of Romania. In 1995, I moved to GeoEcoMar, but as his lab was located in the GeoEcoMar building, our collaboration remained permanent. Over the last two years we have even shared the same office. Our scientific collaboration started in 1973; it comprises several common research projects and dozens of published papers, and is still continuing today, as more joint papers are waiting to be finished. These are the circumstances in which Sorin, my brother, my friend, my colleague, my collaborator, has departed.
Keywords: Sorin-Corneliu Rădan; GeoEcoMar